CONTENT VALIDATION OF A CARE-EDUCATIONAL TECHNOLOGY FOR WOMEN PSYCHOACTIVE CONSUMERS - Fernandes, Mariana Coronato; Nóbrega, Maria do Perpétuo Socorro de Sousa (Cogitare Enfermagem, 2024)
Objective: To build and validate the content of a Care-Educational Technology for women who consume psychoactive substances. Method: Methodological research conducted in the municipality of São Paulo, December 2022 to March 2023 by mapping the literature, drawing up the generating themes, choosing the base tool with dynamics of use, and validating the content in terms of aspects: reflection, relevance, understanding, and suitability in two rounds. Fifteen experts took part, with an agreement rate of 80%. Results: 48 letters were submitted for validation. In the first round, seven cards failed to reach the minimum index. At the end of the second round, 47 cards in all their categories had more agreement than the established level. Conclusion: The experts pointed out the relevance and pertinence of the topics and their potential to help professionals intervene more assertively in the face of the target audience’s needs.